TiBCN / AlSi10Mg composite powder, preparation method of TiBCN / AlSi10Mg composite powder and 3D printing method of TiBCN / AlSi10Mg composite material

By combining TiBCN/AlSi10Mg composite powder preparation method with 3D printing and laser shock peening technology, the problems of uneven mixing and agglomeration of composite powder were solved, and the high performance of composite material was achieved.

CN120961928APending Publication Date: 2025-11-18TAIYUAN INST OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511160009.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-19
Publication Date
2025-11-18

AI Technical Summary

Technical Problem

In the prior art, composite powders are prone to uneven mixing or agglomeration during ball milling, resulting in uneven microstructure and unstable properties of composite materials. Furthermore, the mechanical properties of composite materials with existing reinforcing phases need to be improved.

Method used

A preparation method was adopted, which involved melting, refining, ultrasonication, and pneumatic atomization of TiBCN powder and AlSi10Mg powder. The mass ratio of TiBCN powder was controlled, and a core-shell structure was formed by 3D printing and laser shock peening technology to improve the interfacial bonding between the reinforcing phase and the matrix.

Benefits of technology

TiBCN/AlSi10Mg composite powder with good uniformity was prepared, which improved the mechanical properties of the composite material, including tensile strength and hardness.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides TiBCN / AlSi10Mg composite powder, a preparation method of the TiBCN / AlSi10Mg composite powder and a 3D printing method of a TiBCN / AlSi10Mg composite material, and belongs to the technical field of additive manufacturing. The purified alloy liquid is subjected to ultrasonic treatment and then subjected to pneumatic atomization, obtained composite powder particles are uniform in distribution and composition and free of agglomeration, TiBCN is adopted as a reinforcement phase, in the process of preparing the composite material through 3D printing, the surface of TiBCN is partially molten and reacts to form a shell layer, and the interior unmolten TiBCN forms a core layer, so that the TiBCN exists in a matrix in a core-shell structure, and the composite material is prepared. And the interface bonding effect of a reinforcing phase and a matrix can be improved, so that the mechanical property of the composite material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of additive manufacturing technology, specifically relating to a TiBCN / AlSi10Mg composite powder and its preparation method, and a 3D printing method for TiBCN / AlSi10Mg composite materials. Background Technology

[0002] Additive manufacturing technology, especially metal matrix composite additive manufacturing technology, has been widely used in aerospace, medical device, and automotive manufacturing in recent years. Commonly used additive manufacturing materials include single-material powders such as aluminum-based alloys, titanium-based alloys, nickel-based alloys, and stainless steel, or composite powders of ceramic particles such as silicon carbide and boron nitride with aluminum-based alloys, titanium-based alloys, nickel-based alloys, and stainless steel. Existing methods for preparing composite powders generally involve ball milling. However, due to significant differences in the physical properties (such as density, particle size, and shape) of different powder materials, uneven mixing or agglomeration easily occurs during ball milling, leading to uneven composite powder structure and unstable properties, which in turn affects the various properties of the prepared composite material. Furthermore, the reinforcing phases in existing technologies are generally silicon carbide, titanium carbide, titanium boride, or boron nitride, and the mechanical properties of the resulting composite material need further improvement. Therefore, how to avoid composite powder agglomeration, improve the uniformity of the composite powder, and simultaneously improve the mechanical properties of the composite material has become a challenge in this field. Summary of the Invention

[0003] The purpose of this invention is to provide a TiBCN / AlSi10Mg composite powder, its preparation method, and a 3D printing method for TiBCN / AlSi10Mg composite materials. The TiBCN / AlSi10Mg composite powder prepared by the method provided by this invention has uniform particles and composition, is free of agglomeration, and the composite material prepared from this composite powder has better mechanical properties.

[0004] To achieve the above-mentioned objectives, the present invention provides the following technical solution:

[0005] This invention provides a method for preparing TiBCN / AlSi10Mg composite powder, comprising the following steps:

[0006] (1) TiBCN powder and AlSi10Mg powder were mixed and then melted to obtain an alloy liquid;

[0007] (2) The alloy liquid obtained in step (1) is mixed with a refining agent, and then refined and slag is removed in sequence to obtain a purified alloy liquid;

[0008] (3) The purified alloy liquid obtained in step (2) is subjected to ultrasonication and then pneumatic atomization to obtain TiBCN / AlSi10Mg composite powder.

[0009] Preferably, in step (1), the mass of TiBCN powder accounts for 0.5 to 1.5% of the total mass of TiBCN powder and AlSi10Mg powder.

[0010] Preferably, the melting temperature in step (1) is 720–760°C.

[0011] Preferably, the refining agent in step (2) includes hexafluoroethane; the mass ratio of the refining agent to the alloy liquid is (0.5-1):1000.

[0012] Preferably, the refining temperature in step (2) is 720-760°C and the refining time is 3-5 minutes.

[0013] Preferably, in step (3), the gas used for pneumatic atomization is argon, the pressure of pneumatic atomization is 2 to 2.5 MPa, the temperature of pneumatic atomization is 700 to 750 °C, and the flow rate of the purified alloy liquid during pneumatic atomization is 300 to 500 g / min.

[0014] The present invention also provides TiBCN / AlSi10Mg composite powder prepared by the preparation method described in the above technical solution.

[0015] This invention also provides a 3D printing method for TiBCN / AlSi10Mg composite materials, comprising:

[0016] TiBCN / AlSi10Mg composite powder was 3D printed and laser shock strengthened to obtain TiBCN / AlSi10Mg composite material; the TiBCN / AlSi10Mg composite powder is the TiBCN / AlSi10Mg composite powder described in the above technical solution.

[0017] Preferably, the parameters for 3D printing are: laser power 380-420W, scanning speed 900-1500mm / s, overlap rate 0.2-0.4, and included angle 65-70°.

[0018] Preferably, the parameters for laser shock peening are: spot size 0.2–0.4 mm, overlap rate 0.1–0.3, pulse energy 0.4–1 J, and energy density 5.7–15 J / cm². 2 .

[0019] This invention provides a method for preparing TiBCN / AlSi10Mg composite powder, comprising the following steps:

[0020] (1) TiBCN powder and AlSi10Mg powder are mixed and melted to obtain an alloy liquid; (2) The alloy liquid obtained in step (1) is mixed with a refining agent and then refined and slag-removed sequentially to obtain a purified alloy liquid; (3) The purified alloy liquid obtained in step (2) is ultrasonicated and then pneumatically atomized to obtain TiBCN / AlSi10Mg composite powder. In this invention, the purified alloy liquid is ultrasonicated and then pneumatically atomized to make the obtained composite powder particles uniform in distribution and composition, without agglomeration. TiBCN is used as a reinforcing phase. During the 3D printing preparation of composite materials, the surface of TiBCN partially melts and reacts to form a shell layer, and the unmelted TiBCN inside forms a core layer, so that TiBCN exists in the matrix in a core-shell structure, which can improve the interfacial bonding effect between the reinforcing phase and the matrix, thereby improving the mechanical properties of the composite material. Detailed Implementation

[0021] This invention provides a method for preparing TiBCN / AlSi10Mg composite powder, comprising the following steps:

[0022] (1) TiBCN powder and AlSi10Mg powder were mixed and then melted to obtain an alloy liquid;

[0023] (2) The alloy liquid obtained in step (1) is mixed with a refining agent, and then refined and slag is removed in sequence to obtain a purified alloy liquid;

[0024] (3) The purified alloy liquid obtained in step (2) is subjected to ultrasonication and then pneumatic atomization to obtain TiBCN / AlSi10Mg composite powder.

[0025] In this invention, TiBCN powder and AlSi10Mg powder are mixed and then melted to obtain an alloy liquid.

[0026] In this invention, the TiBCN powder is preferably irregular TiBCN powder.

[0027] In this invention, the particle size of the TiBCN powder is preferably ≤10 μm. Controlling the particle size of the TiBCN powder within this range further improves the mechanical properties of the TiBCN / AlSi10Mg composite material prepared from the TiBCN / AlSi10Mg composite powder. This invention does not have a specific limitation on the source of the TiBCN powder; commercially available products well-known to those skilled in the art can be used. In the embodiments of this invention, the TiBCN powder was purchased from Changchun Dongji Materials Technology Co., Ltd. In this invention, the TiBCN powder is preferably dried before use. This invention does not have a specific limitation on the drying operation; drying techniques well-known to those skilled in the art can be used.

[0028] In this invention, the AlSi10Mg powder is preferably spherical. This invention does not impose any special limitation on the particle size of the AlSi10Mg powder; conventional commercially available products are acceptable. This invention also does not impose any special limitation on the source of the AlSi10Mg powder; commercially available products well-known to those skilled in the art are acceptable. In an embodiment of this invention, the AlSi10Mg powder was purchased from AVIC MITEK Additive Manufacturing Co., Ltd. In this invention, the AlSi10Mg powder is preferably dried before use. This invention does not impose any special limitation on the drying operation; drying techniques well-known to those skilled in the art are acceptable.

[0029] In this invention, the TiBCN powder preferably accounts for 0.5% to 1.5% of the total mass of TiBCN powder and AlSi10Mg powder. As one embodiment, the TiBCN powder may specifically account for 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, or 1.5% of the total mass of TiBCN powder and AlSi10Mg powder. By using TiBCN powder as a reinforcing phase and controlling its mass content within the above range, this invention can further improve the uniformity of the composite powder, thereby further improving the mechanical properties of the composite material.

[0030] In this invention, the melting temperature is preferably 720–760°C. As one embodiment, the melting temperature can specifically be 720°C, 730°C, 740°C, 750°C, or 760°C. This invention does not impose a specific limitation on the melting time; it is sufficient to ensure that the TiBCN powder and AlSi10Mg powder are fully melted.

[0031] After obtaining the alloy liquid, the present invention mixes the alloy liquid with a refining agent, and then performs refining and slag removal in sequence to obtain a purified alloy liquid.

[0032] In this invention, the refining agent preferably includes hexafluoroethane.

[0033] In this invention, the preferred mass ratio of the refining agent to the molten alloy is (0.5-1):1000. As one embodiment, the mass ratio of the refining agent to the molten alloy can specifically be 0.5:1000, 0.6:1000, 0.7:1000, 0.8:1000, 0.9:1000, or 1:1000. By controlling the mass ratio of the refining agent to the molten alloy within the above range, this invention can effectively remove impurities from the molten alloy.

[0034] In this invention, the refining temperature is preferably 720–760°C. As one embodiment, the refining temperature may specifically be 720°C, 730°C, 740°C, 750°C, or 760°C.

[0035] In this invention, the refining time is preferably 3 to 5 minutes. As one embodiment, the refining time can specifically be 3 minutes, 4 minutes, or 5 minutes. By controlling the refining temperature and time within the above range, this invention can effectively remove impurities from the molten alloy.

[0036] The present invention does not impose any special limitations on the slag removal operation, and any slag removal technical solution known to those skilled in the art can be used.

[0037] After obtaining the purified alloy liquid, the present invention performs ultrasonication on the purified alloy liquid and then performs pneumatic atomization to obtain TiBCN / AlSi10Mg composite powder.

[0038] In this invention, the temperature of the ultrasound is preferably 730–750°C. As one embodiment, the temperature of the ultrasound may specifically be 730°C, 740°C, or 750°C.

[0039] In this invention, ultrasonication and heating are performed alternately, more preferably ultrasonication for 8 to 12 minutes, and then the alloy liquid is heated to 730 to 750°C, and the ultrasonication and heating process is repeated.

[0040] In this invention, the ultrasonication and heating are preferably repeated 3 to 5 times. For operational safety, heating is not performed during ultrasonication. Therefore, as ultrasonication continues, the temperature of the alloy liquid decreases. When the temperature of the alloy liquid drops below the ultrasonic temperature, ultrasonication is stopped, and heating is performed to bring the temperature of the alloy liquid back to the ultrasonic temperature range. The ultrasonication method of this invention results in a more uniform composition of the alloy liquid, leading to a composite powder with no agglomeration, uniform particles, and uniform composition after subsequent pneumatic atomization.

[0041] In this invention, the gas used for pneumatic atomization is preferably argon; the pressure of pneumatic atomization is preferably 2–2.5 MPa; the temperature of pneumatic atomization is preferably 700–750 °C; and the flow rate of the purified alloy liquid during pneumatic atomization is preferably 300–500 g / min. As one embodiment, the pressure of pneumatic atomization can specifically be 2 MPa, 2.1 MPa, 2.2 MPa, 2.3 MPa, 2.4 MPa, or 2.5 MPa; the temperature of pneumatic atomization can specifically be 700 °C, 710 °C, 720 °C, 730 °C, 740 °C, or 750 °C; and the flow rate of the purified alloy liquid during pneumatic atomization can specifically be 300 g / min, 350 g / min, 400 g / min, 450 g / min, or 500 g / min. This invention controls the parameters of pneumatic atomization within the above-mentioned range, which can further obtain composite powders that are free from agglomeration, have uniform distribution and composition, and the particle size of the composite powders can be adjusted by changing each parameter.

[0042] In this invention, during the pneumatic atomization process, the alloy liquid that has not yet undergone pneumatic atomization is preferably subjected to alternating ultrasonication and heating until all the alloy liquid is pneumatically atomized; the ultrasonication and heating operations are preferably the same as those described above, and will not be repeated here. This invention, by alternating ultrasonication and heating of the alloy liquid that has not yet undergone pneumatic atomization, ensures the uniformity of the composition of the alloy liquid and further improves the uniformity of the composite powder.

[0043] In one implementation method, the pneumatic atomization can be performed in a powder-making chamber. The present invention does not impose any special limitations on the size of the powder-making chamber; it can be selected according to actual needs. In this invention, liquid nitrogen is distributed in the powder-making chamber for cooling and drying to obtain composite powder.

[0044] After pneumatic atomization is completed, the present invention preferably sieves the product of pneumatic atomization to obtain TiBCN / AlSi10Mg composite powder.

[0045] The present invention does not impose any special limitations on the sieving operation. Any sieving technique known to those skilled in the art can be used to ensure that the particle size of the TiBCN / AlSi10Mg composite powder is within the required range.

[0046] In this invention, the particle size of the TiBCN / AlSi10Mg composite powder is preferably 30-45 μm.

[0047] This invention involves ultrasonicating the purified alloy liquid, followed by pneumatic atomization, and controlling various process parameters to ensure that the resulting composite powder has a uniform particle distribution and composition without agglomeration. TiBCN is used as the reinforcing phase. During the 3D printing process of the composite material, the surface of TiBCN partially melts and reacts to form a shell layer, while the unmelted TiBCN inside forms a core layer. This allows TiBCN to exist in the matrix in a core-shell structure, which can improve the interfacial bonding effect between the reinforcing phase and the matrix, thereby improving the mechanical properties of the composite material.

[0048] The present invention also provides TiBCN / AlSi10Mg composite powder prepared by the preparation method described in the above technical solution.

[0049] The composite powder prepared by this invention is free from agglomeration, has a uniform distribution and composition, and the composite material prepared by 3D printing has better mechanical properties.

[0050] This invention also provides a 3D printing method for TiBCN / AlSi10Mg composite materials, comprising:

[0051] TiBCN / AlSi10Mg composite powder was 3D printed and laser shock strengthened to obtain TiBCN / AlSi10Mg composite material; the TiBCN / AlSi10Mg composite powder is the TiBCN / AlSi10Mg composite powder described in the above technical solution.

[0052] In this invention, the TiBCN / AlSi10Mg composite powder is preferably dried before use. The drying temperature is preferably 120–200°C, and the drying time is preferably 2–12 hours. Drying the composite powder in this invention avoids the adverse effects of residual moisture on the composite material during the 3D printing process.

[0053] In this invention, the 3D printing is preferably performed using selective laser melting (SLM) technology.

[0054] In this invention, the preferred parameters for 3D printing are: laser power 380–420W, scanning speed 900–1500 mm / s, overlap rate 0.2–0.4, and included angle 65–70°. As one embodiment, the laser power can specifically be 380W, 385W, 390W, 395W, 400W, 410W, or 420W; the scanning speed can specifically be 900mm / s, 1000mm / s, 1100mm / s, 1200mm / s, 1300mm / s, 1400mm / s, or 1500mm / s; the overlap rate can specifically be 0.2, 0.3, or 0.4; and the included angle can specifically be 65°, 66°, 67°, 68°, 69°, or 70°. In this invention, TiBCN in the composite powder serves as a reinforcing phase. During the 3D printing process to prepare the composite material, the surface of TiBCN partially melts and reacts to form a shell layer (Ti(C,N), TiC, TiN, TiB2, etc.), while the unmelted TiBCN inside forms a core layer. This allows TiBCN to form a core-shell structure in situ within the matrix, improving the interfacial bonding between the reinforcing phase and the matrix, thereby enhancing the mechanical properties of the composite material. By controlling the 3D printing parameters within the aforementioned range, this invention further improves the mechanical properties of the composite material.

[0055] In this invention, the 3D printing is preferably performed on a substrate. This invention does not impose any special limitations on the material or size of the substrate; any 3D printing substrate well-known to those skilled in the art can be used.

[0056] In this invention, the substrate is preferably preheated before 3D printing; the preheating temperature is preferably 170–190°C, more preferably 180°C. This invention does not specify a particular preheating time, as long as the substrate reaches the preheating temperature.

[0057] In this invention, the preferred parameters for laser shock enhancement are: spot size 0.2–0.4 mm, overlap rate 0.1–0.3, pulse energy 0.4–1 J, and energy density 5.7–15 J / cm². 2 In one implementation, the spot size can be specifically 0.2 mm, 0.3 mm, or 0.4 mm; the overlap rate can be specifically 0.1, 0.2, or 0.3; the pulse energy can be specifically 0.4 J, 0.5 J, 0.6 J, 0.7 J, 0.8 J, 0.9 J, or 1 J; and the energy density can be specifically 5.7 J / cm². 2 6J / cm 2 7J / cm 2 8J / cm 2 9J / cm 2 10J / cm 2 11J / cm 2 12J / cm 2 13J / cm 2 14J / cm 2 Or 15J / cm 2 In this invention, the laser shock peening path is preferably consistent with the 3D printing path. Laser shock peening, as described in this invention, can eliminate stress generated during the 3D printing process of composite materials, improve defects such as porosity and cracks, and thus enhance the mechanical properties of the composite material. By controlling the laser shock peening parameters within the aforementioned range, this invention can further improve the mechanical properties of the composite material.

[0058] In this invention, the laser shock strengthening can be single-layer or multi-layer, depending on the size and complexity of the printed composite material.

[0059] The present invention preferably involves 3D printing 5 to 10 layers, followed by laser shock strengthening of each layer, and then repeating the 3D printing and laser shock strengthening process until the 3D printing is completed.

[0060] In this invention, the parameters for each laser shock strengthening process can be the same or different. When the number of printed layers is small, the stress on each layer is consistent, so the parameters for each laser shock strengthening can be the same. When the number of printed layers is large, the middle part is mainly subjected to compressive stress, while the two ends are mainly subjected to tensile stress. Therefore, the parameters for laser shock strengthening of the middle part and the two ends can be different in order to better eliminate stress and defects.

[0061] This invention incorporates laser shock peening and controls various process parameters to further improve the mechanical properties of the composite material.

[0062] The technical solutions of this invention will be clearly and completely described below with reference to the embodiments thereof. Obviously, the described embodiments are only a part of the embodiments of this invention, and not all of them. All other embodiments obtained by those skilled in the art based on the embodiments of this invention without creative effort are within the scope of protection of this invention.

[0063] Example 1

[0064] A method for preparing TiBCN / AlSi10Mg composite powder: (1) 4975g of dried spherical AlSi10Mg powder (AVIC MITE Additive Manufacturing Co., Ltd.) and 25g of dried irregular TiBCN powder (Changchun Dongji Materials Technology Co., Ltd., particle size ≤10μm) are placed in an alumina crucible and heated to 730℃ to melt, thereby obtaining an alloy liquid. The mass of TiBCN powder accounts for 0.5% of the total mass of TiBCN powder and AlSi10Mg powder.

[0065] (2) The alloy liquid obtained in step (1) is mixed with hexafluoroethane refining agent, and after refining at 730°C for 4 minutes, the slag is removed to obtain purified alloy liquid. The mass ratio of refining agent to alloy liquid is 0.8:1000.

[0066] (3) The purified alloy liquid was ultrasonicated for 10 min, then heated to 750℃. After ultrasonication and heating were performed 4 times in turn, it was pneumatically atomized in the powder preparation chamber (liquid nitrogen was distributed in the powder preparation chamber for cooling and drying). The gas for pneumatic atomization was argon, the pressure was 2 MPa, the temperature was 750℃, and the flow rate of the purified alloy liquid was 300 g / min. The alloy liquid that had not yet been atomized during the pneumatic atomization process was ultrasonicated and heated in turn. After the pneumatic atomization was completed, it was sieved to obtain TiBCN / AlSi10Mg composite powder (30~45μm).

[0067] Example 2

[0068] The TiBCN / AlSi10Mg composite powder from Example 1 was dried at 200℃ for 7 hours and then 3D printed using selective laser melting (SLM). Before printing, the substrate was preheated to 180℃. The composite powder was melted layer by layer using a high-energy laser beam. The 3D printing parameters were: laser power 385W, scanning speed 900mm / s, overlap rate 0.3, and angle 67°. Laser shock peening was performed once every 5 layers, for a total of 3300 layers. The laser shock peening path was consistent with the 3D printing path. The laser shock peening parameters were: spot size 0.3mm, overlap rate 0.1, pulse energy 0.4J, and energy density 5.7J / cm³. 2 TiBCN / AlSi10Mg composite material was obtained.

[0069] The TiBCN / AlSi10Mg composite material prepared in Example 2 has a tensile strength of 457 MPa, a hardness of 153 Hv, and an abrasion tolerance of 0.207 × 10⁻⁶. -3 mm 3 N -1 m -1 The tensile tests were conducted using an Instraddle 68tm-50 instrument with a gauge length of 20 mm and a tensile rate of 1 mm / s. Hardness testing was performed using a digital display microhardness tester (JMHVS-1000AT) with a test load of 1.98 N and a holding time of 15 s. The average hardness value of each sample was obtained by taking five samples from each sample. The friction and wear tests were conducted using an HRS-2M high-speed reciprocating friction testing machine. The mating material was 4 mm diameter GCr15 spheres with a hardness of HRC63±3. The test conditions were: load 25 N, speed 0.05 mm / s, and test time 30 min.

[0070] Example 3

[0071] A method for preparing TiBCN / AlSi10Mg composite powder: (1) 4950g of dried spherical AlSi10Mg powder (AVIC MAT Additive Manufacturing Co., Ltd.) and 50g of dried irregular TiBCN powder (Changchun Dongji Materials Technology Co., Ltd., particle size ≤10μm) are placed in an alumina crucible and heated to 730℃ to melt, thereby obtaining an alloy liquid. The mass of TiBCN powder accounts for 1% of the total mass of TiBCN powder and AlSi10Mg powder.

[0072] (2) The alloy liquid obtained in step (1) is mixed with hexafluoroethane refining agent, and after refining at 730°C for 4 minutes, the slag is removed to obtain purified alloy liquid. The mass ratio of refining agent to alloy liquid is 0.8:1000.

[0073] (3) The purified alloy liquid was ultrasonicated for 10 min, and then heated to 750℃. After ultrasonication and heating were performed 4 times in turn, it was pneumatically atomized in the powder preparation chamber (liquid nitrogen was distributed in the powder preparation chamber for cooling and drying). The gas for pneumatic atomization was argon, with a pressure of 2.2 MPa, a temperature of 750℃, and a flow rate of 400 g / min. The alloy liquid that had not yet been atomized during the pneumatic atomization process was ultrasonicated and heated in turn. After the pneumatic atomization was completed, it was sieved to obtain TiBCN / AlSi10Mg composite powder (30~45μm).

[0074] Example 4

[0075] The TiBCN / AlSi10Mg composite powder from Example 3 was dried at 200℃ for 7 hours and then 3D printed using selective laser melting (SLM). Before printing, the substrate was preheated to 180℃. The composite powder was melted layer by layer using a high-energy laser beam. The 3D printing parameters were: laser power 400W, scanning speed 1100mm / s, overlap rate 0.3, and angle 67°. Laser shock peening was performed once every 5 layers, for a total of 3300 layers. The laser shock peening path was the same as the 3D printing path. The laser shock peening parameters were: spot size 0.3mm, overlap rate 0.2, pulse energy 0.7J, and energy density 10J / cm³. 2 TiBCN / AlSi10Mg composite material was obtained.

[0076] The TiBCN / AlSi10Mg composite material prepared in Example 4 has a tensile strength of 392 MPa, a hardness of 159 Hv, and an abrasion tolerance of 0.182 × 10⁻⁶. -3 mm 3 N -1 m -1 .

[0077] Example 5

[0078] A method for preparing TiBCN / AlSi10Mg composite powder: (1) 4925g of dried spherical AlSi10Mg powder (AVIC MITE Additive Manufacturing Co., Ltd.) and 75g of dried irregular TiBCN powder (Changchun Dongji Materials Technology Co., Ltd., particle size ≤10μm) are placed in an alumina crucible and heated to 730℃ to melt, thereby obtaining an alloy liquid. The mass of TiBCN powder accounts for 1.5% of the total mass of TiBCN powder and AlSi10Mg powder.

[0079] (2) The alloy liquid obtained in step (1) is mixed with hexafluoroethane refining agent, and after refining at 730°C for 4 minutes, the slag is removed to obtain purified alloy liquid. The mass ratio of refining agent to alloy liquid is 0.8:1000.

[0080] (3) The purified alloy liquid was ultrasonicated for 10 min and then heated to 750℃. After ultrasonication and heating were performed 4 times in turn, it was pneumatically atomized in the powder preparation chamber (liquid nitrogen was distributed in the powder preparation chamber for cooling and drying). The gas for pneumatic atomization was argon, with a pressure of 2.5 MPa, a temperature of 750℃, and a flow rate of 500 g / min. The alloy liquid that had not yet been atomized during the pneumatic atomization process was ultrasonicated and heated in turn. After the pneumatic atomization was completed, it was sieved to obtain TiBCN / AlSi10Mg composite powder (30~45μm).

[0081] Example 6

[0082] The TiBCN / AlSi10Mg composite powder from Example 5 was dried at 200℃ for 7 hours and then 3D printed using selective laser melting (SLM). Before printing, the substrate was preheated to 180℃. The composite powder was melted layer by layer using a high-energy laser beam. The 3D printing parameters were: laser power 420W, scanning speed 1300mm / s, overlap rate 0.3, and angle 67°. Laser shock peening was performed once every 5 layers, for a total of 3300 layers. The laser shock peening path was consistent with the 3D printing path. The laser shock peening parameters for layers 1 to 1100 were: spot size 0.3mm, overlap rate 0.3, pulse energy 1J, and energy density 15J / cm³. 2 The parameters for laser shock peening during the process of 1100–2200 layers are: spot size 0.3 mm, overlap rate 0.3, pulse energy 0.4 J, and energy density 5.7 J / cm³. 2 The parameters for laser shock peening during the process of 2200–3300 layers are: spot size 0.3 mm, overlap rate 0.3, pulse energy 1 J, and energy density 15 J / cm³. 2 TiBCN / AlSi10Mg composite material was obtained.

[0083] The TiBCN / AlSi10Mg composite material prepared in Example 6 has a tensile strength of 345 MPa, a hardness of 177 Hv, and an abrasion tolerance of 0.173 × 10⁻⁶. -3 mm 3 N -1 m -1 .

[0084] In summary, the composite powder prepared by this invention is free from agglomeration, has a uniform distribution and composition, and the prepared composite material has better mechanical properties.

[0085] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A method for preparing TiBCN / AlSi10Mg composite powder, comprising the following steps: (1) TiBCN powder and AlSi10Mg powder were mixed and then melted to obtain an alloy liquid; (2) The alloy liquid obtained in step (1) is mixed with a refining agent, and then refined and slag is removed in sequence to obtain a purified alloy liquid; (3) The purified alloy liquid obtained in step (2) is subjected to ultrasonication and then pneumatic atomization to obtain TiBCN / AlSi10Mg composite powder.

2. The preparation method according to claim 1, characterized in that, In step (1), the mass of TiBCN powder accounts for 0.5 to 1.5% of the total mass of TiBCN powder and AlSi10Mg powder.

3. The preparation method according to claim 1, characterized in that, The melting temperature in step (1) is 720–760°C.

4. The preparation method according to claim 1, characterized in that, The refining agent in step (2) includes hexafluoroethane; the mass ratio of the refining agent to the alloy liquid is (0.5-1):1000.

5. The preparation method according to claim 1, characterized in that, The refining temperature in step (2) is 720-760℃, and the refining time is 3-5 minutes.

6. The preparation method according to claim 1, characterized in that, In step (3), the gas used for pneumatic atomization is argon, the pressure of pneumatic atomization is 2 to 2.5 MPa, the temperature of pneumatic atomization is 700 to 750 °C, and the flow rate of the purified alloy liquid during pneumatic atomization is 300 to 500 g / min.

7. TiBCN / AlSi10Mg composite powder prepared by the preparation method according to any one of claims 1 to 6.

8. A 3D printing method for TiBCN / AlSi10Mg composite material, comprising: TiBCN / AlSi10Mg composite powder was 3D printed and laser shock strengthened to obtain TiBCN / AlSi10Mg composite material; the TiBCN / AlSi10Mg composite powder is the TiBCN / AlSi10Mg composite powder according to claim 7.

9. The 3D printing method according to claim 8, characterized in that, The parameters for the 3D printing are: laser power 380-420W, scanning speed 900-1500mm / s, overlap rate 0.2-0.4, and included angle 65-70°.

10. The 3D printing method according to claim 8, characterized in that, The parameters for laser shock peening are: spot size 0.2–0.4 mm, overlap rate 0.1–0.3, pulse energy 0.4–1 J, and energy density 5.7–15 J / cm². 2 .